Improving oxygen vacancies by cobalt doping in MoO2 nanorods for efficient electrocatalytic hydrogen evolution reaction - Hailong Li (Wiley-VCH, 2021)
Abstract Recently, molybdenum dioxide (MoO2) has gained intensive attention as an eco‐friendly and earth abundant catalyst for electrocatalytic hydrogen evolution from water splitting. However, the catalytic activity of MoO2 catalyst for hydrogen evolution reaction (HER) is severely limited by the less exposed active sites. Herein, we present Co‐doped MoO2 for efficient HER through a facile wet chemistry synthesis followed by calcination treatment process. The optimized Co‐MoO2‐0.01 nanorods (NRs) delivers a very low overpotential of 26 mV at 10 mA cm−2 and a small Tafel slope of 30.9 mV dec−1, which is much better than that of pure MoO2 NRs and the commercial Pt/C catalyst in HER. Experimental and theoretical results reveal that Co doping not only produce more oxygen vacancies in MoO2, which can activate adjacent oxygen atoms as active sites and thus increase the exposed active sites on the surface of catalyst, but also enhance the electrical conductivity of catalyst during HER process. In a word, this work provides a new promising synthetic strategy for developing earth‐abundant and cost‐effective HER electrocatalysts through rational defect‐engineering design.